Nepalese Political Leadership in Relief Distribution and Constitution Drafting Process after Earthquake-2015 (Patan Prospective Journal, 2023)
This paper discusses the characteristics of leadership in Nepalese politics specifically after the earthquake of 2015.With some examples from the context, it argues that leadership like other techniques prioritizes on the elements like caring, problem solving and facilitation. It makes attempts to promote sustainability in the social and capital structure of the nation. Again, it challenges long rooted social problems like discrimination, injustices and inequalities leading towards unity in diversity of culture, tradition and ethnicity. In exercising the power in Nepali society, there are a number of leadership styles like charismatic, authentic, feudalistic, authoritative, democratic, transformational, spiritual, and ethical in practice. However, we find lacking of responsibility in the tendency of exercising leadership in our context. This article highlights the drawbacks like arise of conflict due to the lack of responsibility in leadership. It further discusses attributable factors causing harm in the peaceful and prosperous setting of society. Thus it hopes in developing the culture of responsibility in crafting leadership styles in various sectors of the Nepalese community in times to come for a better social order.